Function of the nephron and the formation of urine. Issue 5 (May 2018) - Lawrence, Eloise A.; Doherty, Daniel; Dhanda, Raman
Abstract: The nephron is the functional unit of the kidney involved in the critical interplay of fluid and electrolyte homeostasis by glomerular filtration, selective tubular reabsorption and secretion. This article will discuss the structure and function of each segment of the nephron, and the physiology pertaining to the formation of urine.